2013
DOI: 10.1364/oe.21.010278
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 154 μm emission in Y-Er disilicate thin films on silicon photonic crystal cavities

Abstract: Abstract:We introduce an Y-Er disilicate thin film deposited on top of a silicon photonic crystal cavity as a gain medium for active silicon photonic devices. Using photoluminescence analysis, we demonstrate that Er luminescence at 1.54 μm is enhanced by coupling with the cavity modes, and that the directionality of the Er optical emission can be controlled through far-field optimization of the cavity. We determine the maximum excitation power that can be coupled into the cavity to be 12 mW, which is limited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Erbium ions have been investigated as one of the promising light emitters in Si. PhC nanocavities have been also applied to enhance the light emission from Er ions (Wang et al, 2012;Savio et al, 2013). Narrowing the cavity linewidth in Er-doped silicon nitride PhC nanocavities has been also demonstrated under optical pumping condition (Gong et al, 2010).…”
Section: Application Of Photonic Crystal Structures To Other Emitters...mentioning
confidence: 99%
“…Erbium ions have been investigated as one of the promising light emitters in Si. PhC nanocavities have been also applied to enhance the light emission from Er ions (Wang et al, 2012;Savio et al, 2013). Narrowing the cavity linewidth in Er-doped silicon nitride PhC nanocavities has been also demonstrated under optical pumping condition (Gong et al, 2010).…”
Section: Application Of Photonic Crystal Structures To Other Emitters...mentioning
confidence: 99%
“…Recently, it was shown that formation of rare-earth silicates (e.g. Er 2 SiO 5 , Eu 2 SiO 5 , Ce 2 Si 2 O 7 ) could enhance their photoluminescence efficiency161718. It was found that in these silicates, the rare-earth ions are 100% activated, and the solubility can reach 10 22  cm −3  192021.…”
mentioning
confidence: 99%
“…The fluorescence intensity of the nano‐engineered SPYAS fiber is found to be a very strong due to the presence of Y and Sc rich crystalline NPs, where Sc enhances the crystal field strength in Er ions sites as the ionic radius of Sc is smaller than that of Er ions . Another reason may be the reduced up‐conversion phenomena as Y cations substitute Er ions due to similarity of ionic radii of Er and Y ions …”
Section: Resultsmentioning
confidence: 99%